A Critical Engagement with the Conceptualization of Sexual Harassment in International Human Rights Law - Dergacheva, Yulia (Nordic journal of human rights, 2024)
This article discussess the concept of sexual harassment in international human rights law (IHRL). After analysing how sexual harassment emerges in two different legal traditions, I investigate the transformations the concept has undergone. I create an outline of sexual harassment as a concept and of certain contexts in which it is conceptualized in international human rights law. The research is grounded in critical feminist studies and intersectionality theory. I investigated an extensive number of legal texts, including various IHRL treaties, soft law, and interpretations by treaty bodies, with a focus on the concept of a hypothetical 'victim' within the sexual harassment narrative. This was done by delving into the linguistic choices present in legal documents that deal with sexual harassment. I conclude that sexual harassment in IHRL is largely constructed around the 'universal subject' of the white cisgender middle-class women, with other identities perceived as exceptions. This leads to the exclusion of subjects who are different from the imaginary victim, thus creating people, spaces, and settings in which sexual harassment is neglected by the law.